2013
DOI: 10.1080/15575330.2011.583355
|View full text |Cite
|
Sign up to set email alerts
|

Bonded to whom? Social interactions in a high-amenity rural setting

Abstract: Beginning with Kasarda and Janowitz, several dimensions of community attachment have been theorized. The local social bonds or the interpersonal dimension of community attachment is reflected in social interaction with family, friends and neighbors. A current trend within the United States is the influx of seasonal residents into high-amenity areas. Whether this influx affects the types of social bonds formed in such areas is an important and unanswered question. This study attempts to determine whether second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…It is thus problematic to provide a concise overview of the research on community attachment (Theodori and Luloff ). In general, community attachment is most commonly conceptualized as sentiments toward one's community (Jennings and Krannich ; Matarrita‐Cascante et al. ).…”
Section: Community Attachmentmentioning
confidence: 99%
See 2 more Smart Citations
“…It is thus problematic to provide a concise overview of the research on community attachment (Theodori and Luloff ). In general, community attachment is most commonly conceptualized as sentiments toward one's community (Jennings and Krannich ; Matarrita‐Cascante et al. ).…”
Section: Community Attachmentmentioning
confidence: 99%
“…Using a systemic model, they found that length of residence was the most important predictor of one's attachment. More recently, some scholars have begun examining elements of community attachment among communities that are experiencing change due to increased numbers of seasonal residents, who are often looking to escape their primary residences for a perceived higher quality of life (Jennings and Krannich ; Stedman ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In second home communities, second home owners consume local natural and cultural resources in that they have higher rates of outdoor recreation than permanent residents (Stedman 2006b), and seek out rural culture (Halfacree ; Vepsalainen and Pitkanen ). Second home owners are generally more economically capable of such consumption, as evident in amenity‐rich counties of rural, southern Utah, where second home owners were more likely than permanent residents to have incomes over $100,000 and to have at least a bachelor's degree (Jennings and Krannich ). In contrast, at times of peak visitation, permanent residents are frequently engaged in service occupations associated with the local amenity economy (Saint Onge, Hunter, and Boardman ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jennings and Krannich () found that social interactions across seasonal‐permanent resident groups are somewhat segregated, with permanent residents interacting more frequently with one another than with second home owners, and with second home owners equally interacting with permanent and other seasonal residents. However, second home owners who spend more than 90 days per year in their second community have similar rates of social interactions among friends and neighbors to those of long‐standing permanent residents (Krannich et al.…”
Section: Literature Reviewmentioning
confidence: 99%